2019
DOI: 10.1186/s12885-019-5631-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of topoisomerase II α and minichromosome maintenance protein 6 expression in colorectal cancer

Abstract: Background Despite rising incidence rates of colorectal malignancies, only a few prognostic tools have been implemented in proven clinical routine. Cell division and proliferation play a significant role in malignancies. In terms of colorectal cancer, the impact of proliferation associated proteins is controversially debated. The aim of our study was to examine the expression of topoisomerase II α and minichromosome maintenance protein 6 and to correlate these findings with the clinical data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The encoded product of MCM6 is a key protein for DNA replication and is involved in the regulation of the cell cycle (Lei, 2005). MCM6 is highly expressed in colon cancer tissues (Hendricks et al, 2019). Huang et al (2018) showed that the suppression of MCM6 in colon cancer cells could inhibit the foci-forming and chromatin localization of RAD51 recombinase (RAD51), a protein essential for DNA damage recovery.…”
Section: Featurementioning
confidence: 99%
“…The encoded product of MCM6 is a key protein for DNA replication and is involved in the regulation of the cell cycle (Lei, 2005). MCM6 is highly expressed in colon cancer tissues (Hendricks et al, 2019). Huang et al (2018) showed that the suppression of MCM6 in colon cancer cells could inhibit the foci-forming and chromatin localization of RAD51 recombinase (RAD51), a protein essential for DNA damage recovery.…”
Section: Featurementioning
confidence: 99%
“…It functions by unwinding the two DNA spiral strands [9] and by promoting G1/S transition [10]. Many studies have shown that the level of expression of MCM6, basing on mRNA detection or immunohistochemistry, was correlated with clinical outcome, e.g., in gliomas, renal cell carcinoma, endometrial adenocarcinoma, lung cancer, osteosarcoma, pheochromocytoma, neuroblastoma, and meningioma [4,[10][11][12][13][14][15][16][17][18][19][20]. Our previous evidence singled out MCM6 as an efficient marker by virtue of its dominant presence in proliferating cells that resulted in striking clear-cut differences in MCM6 labeling index (LI) of the indolent vs. the recurrent meningiomas, with a high reproducibility [4].…”
Section: Introductionmentioning
confidence: 99%
“…A precise and robust gene signature can significantly aid in the clinical identification of disease [ 11 ]. Bioinformatics methods have been widely used to analyze high-throughput sequencing data and microarray data for the prediction of disease-related genes, such as renal cell carcinoma [ 12 ], triple-negative breast cancer [ 13 ], and colorectal cancer [ 14 ]. However, few of these studies examined the effect of nutritional deficiency in the tumor microenvironment on tumor prognosis, which was very important in tumor progression.…”
Section: Introductionmentioning
confidence: 99%